The Ancient Technique of Weaving with the Contemporary Art - Supamas Jiamrungsan (Graduate School of Institut Seni Indonesia Yogyakarta, 2017)
This study is a qualitative research method. The purposes are firstly to trial production of Pha Yok Dok which is one of the local handicrafts, found in the north-eastern part of Thailand. It is the guidelines for handling core issues of the creation and must start from studying motif of design, focus on techniques the golden fabric is located at weaving with gold threads, called Yok Thong. Secondly, to improve the pattern of contemporary fabric are the synthesis of Yok Dok texti le design in making fabric. It is a complex process which requires highly skilled weavers. In researcher’s point of view, for weaving of each fabric-depending on the design and used for similar was weaving 1500 shaft/Ta-kor. Thirdly to invent textile art inspiration from Yok Dok textile design to create new works of art. The results showed that the fabric weave of the operation weave structure on motifs of Yok Dok textile design. This is an outstanding special technique. The contemporary new fabric pattern can be operated by opening and closing of the warp yarn on a draw frame. The new pattern design and process of Yok Dok textile design by fabric weave selection. It is a supplementary weft technique that is the process a nd design which is the first method of fabric craft practice use for the manual textile art inspiration from Yok Dok textile design to those who is the weaver. Textile weaving process by adding a special fabric pattern these characteristics come from the roots and identity of steps and methods of natural fabric cultivation. It is completed by delicate skill of weaving alternatives for creating a product and to serve as a guideline for further research. This handicraft highlights the significance continuation and bridge the relationship between classic fabric contemporary. Art to humanity from the ancient world until the present day. In summary the researchers plan to design and c ontemporary Yok Dok, a synthesis between classical the golden fabric of the Royal cord of Rattanakosin period and the contemporary Thai litterateur work which telling design.